(untitled) (International Journal of Engineering & Extended Technologies Research (IJEETR), 2023)
The rapid increase in the digital platforms has altered the world economies and introduced innovation, connectivity and economic development. However this growth has also raised advanced governance problems particularly in regards to ensuring that legal and ethical standards are followed. The article is a study on the structures that should be in existence to ensure compliance in the digital platform governance. It examines the existing frameworks and proposes a common manner of establishing a balanced regulatory condition which will be founded on regulatory control, transparency procedures and stakeholder participation. This paper analyses how legal frameworks, technology infrastructure, and organizational policies can interact to promote compliance and inhibit risks related to privacy of information, bias in algorithms, market monopoly and consumer protection. The other factors of compliance that are emphasized in the study and are critical to promoting trust and equity in the digital mediums are auditability, accountability, and user empowerment. In addition, the paper will discuss how the existing technologies can be leveraged to automate the compliance processes, in order to offer real-time monitoring and resolving the issues i.e. artificial intelligence and machine learning. It also defines regulatory fragmentation, jurisdiction and dynamic nature of digital technologies as a matter of concern and provides recommendations on how to create dynamic and flexible structures. These frameworks are very important in balancing between innovation and responsible governance. The article is targeted at educating the policymakers, platform operators, and users concerning how the collaboration and continuous adaptation would enhance the efficiency of the digital platform governance and compliance.